The Reliability and Validity of a Modified Squat Test to Predict Cardiopulmonary Fitness in Healthy Older Men. (2nd January 2018) - Yeh, Chiu-Ping; Huang, Hsien-Cheng; Chang, Yaju; Chen, Ming-De; Hsu, Miaoju
Abstract : Background . Shortcomings are noted in currently available cardiopulmonary field tests for the older adult and thus relevant research is still ongoing. Purpose . The purpose of this study was to investigate the reliability and validity of a modified squat test and to establish a regression model for predicting aerobic fitness in the older adult. Methods . Twenty-five healthy men aged 60 to 75 years completed this study. Each subject performed two modified squat tests with a prototype testing equipment and a maximal exercise test to determine maximal oxygen consumption. Recovery heart rates (HR) (0~30, 60~90, and 120~150 seconds) were measured following the modified squat tests. The fitness indexes included the sum of recovery HR, recovery HR index, age-adjusted recovery HR index, and immediate HR. Results . The results revealed that the age-adjusted recovery HR index fitness had the highest intraclass correlation coefficients (ICC) of 0.9 and Pearson's correlation coefficients of 0.71, which suggested the modified squat test can reasonably assess cardiopulmonary fitness for the older adult. The regression equation for estimating aerobic power wasV ˙ O 2 m a x = 16.781 + 16.732 × (age-adjusted recovery HR index) + 0.02467 × (physical activity level). Conclusion . The modified squat test is a valid and reliable field test and thus can be an option to assess the cardiopulmonary fitness level of healthy older men in clinics or communities.